1999
DOI: 10.1159/000026599
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Alpha-1-Antichymotrypsin Polymorphism and Alzheimer’s Disease in Chinese

Abstract: A recent observation has shown that a common polymorphism in the α1-antichymotrypsin (ACT) confers a significant risk for Alzheimer’s disease (AD). Furthermore, the apolipoprotein E ε4 allele (APOE*4) effect associated with AD risk is modified by the ACT polymorphisms. To evaluate the role of ACT polymorphism in AD, we conducted an association study of ACT polymorphisms in Chinese AD patients and normal controls. We found that the ACT polymorphism had no effect on the development of AD either alone or in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…Taking the ethnic differences into account, the allele frequencies for the controls (alanine: 40.86%, threonine: 59.14%) and case samples (alanine: 41.45%, threonine: 58.55%) of our study are different from the ones of Slowik et al [21] (alanine: 50%, threonine: 50%) that correspond to those described in the CEU Hapmap data (alanine: 50.9%, threonine: 49.1%) [27]. In a further A/G polymorphism study on AD by Wang et al [28], 114 Chinese control samples showed similar frequencies to ours (alanine: 39.00%, threonine: 61.00%). …”
Section: Discussioncontrasting
confidence: 93%
“…Taking the ethnic differences into account, the allele frequencies for the controls (alanine: 40.86%, threonine: 59.14%) and case samples (alanine: 41.45%, threonine: 58.55%) of our study are different from the ones of Slowik et al [21] (alanine: 50%, threonine: 50%) that correspond to those described in the CEU Hapmap data (alanine: 50.9%, threonine: 49.1%) [27]. In a further A/G polymorphism study on AD by Wang et al [28], 114 Chinese control samples showed similar frequencies to ours (alanine: 39.00%, threonine: 61.00%). …”
Section: Discussioncontrasting
confidence: 93%
“…Part of this sample population was used in our previous studies [2,11]. The AD and probable AD diagnoses were derived consensually by a team of neurologists, according to criteria established by the National Institute of Neurological and Communicative Disorder and Stroke, and the Alzheimer's and Related Disorders Association, respectively [12].…”
Section: Methodsmentioning
confidence: 99%
“…A common factor in the postulated mechanisms of Aβ toxicity is the oligomerization of Αβ, whether as dimers or trimers [217,218], protofibrils [219], or fully formed fibrils [220,221]. Despite several attempts, the main obstacle to the full validation of the Aβ hypothesis lies in the identification in vivo of the specific neurotoxic Aβ soluble oligomer.…”
Section: Aβ Is Toxicmentioning
confidence: 99%
“…Blocking Aβ fibril formation prevents this toxicity [220,221,278,279]. Astrocytes and microglial cells are involved in the chronic inflammatory responses in AD through the upregulated expression of phospholipase A2, leading to increased arachidonic acid/prostaglandin inflammatory pathway activity by secreting interleukin-1 [280], activation of complement pathways [281], and by producing a variety of potentially neurotoxic compounds, including superoxides, glutamate, and NO [282,283].…”
Section: Activation Of Inflammatory Processesmentioning
confidence: 99%